Sin (A + B) = sin A cos B + cos A Sin B
<span>Cos (A - B) = cos A cos B + sin A sin B </span>
<span>=> (SinACosB+ CosASinB) (CosACosB +SinASinB) </span>
<span>=>SinACosACos^2B+Sin^2ACosBSinB+Cos^2A... </span>
<span>=>SinACosA(Cos^2B+Sin^2B) +SinBCosB(Sin^2A+Cos^2A) </span>
<span>we know that Sin^2+Cos^2=1 </span>
<span>=>SinACosA(1)+SinBCosB(1) </span>
<span>=SinACosA+SinBCosB </span>
<span>Proved
</span>
Answer:
5-2(-4x+10)-5x----open brackets and multiply
5+8x-20-5x----combine like terms
8x-5x+5-20
3x-15
3(x-5)
Answer:
54
Step-by-step explanation:
Use the Area of Triangle formula A=HB divided by 2